2017
DOI: 10.1002/ece3.3466
|View full text |Cite
|
Sign up to set email alerts
|

Population genomics of the eastern cottonwood (Populus deltoides)

Abstract: Despite its economic importance as a bioenergy crop and key role in riparian ecosystems, little is known about genetic diversity and adaptation of the eastern cottonwood (Populus deltoides). Here, we report the first population genomics study for this species, conducted on a sample of 425 unrelated individuals collected in 13 states of the southeastern United States. The trees were genotyped by targeted resequencing of 18,153 genes and 23,835 intergenic regions, followed by the identification of single nucleot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
56
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(64 citation statements)
references
References 84 publications
7
56
1
Order By: Relevance
“…Most of the individuals distributed in the Mississippi River Basin were grouped together (Group II, Fig. 4a, c), and individuals in different states of the Mississippi River Basin had high genetic similarity, which was consistent with the results of Fahrenkrog et al [29,37]. The genetic differentiation between different basins indicated that geographical isolation restricts gene 10 exchange among populations [38].…”
Section: Population Structuresupporting
confidence: 86%
See 3 more Smart Citations
“…Most of the individuals distributed in the Mississippi River Basin were grouped together (Group II, Fig. 4a, c), and individuals in different states of the Mississippi River Basin had high genetic similarity, which was consistent with the results of Fahrenkrog et al [29,37]. The genetic differentiation between different basins indicated that geographical isolation restricts gene 10 exchange among populations [38].…”
Section: Population Structuresupporting
confidence: 86%
“…The results showed that the P. deltoides population had abundant genetic diversity and moderate genetic differentiation. The results showed that the degree of genetic differentiation was relatively high, probably because the materials in this study were from three basins in the main distribution area of P. deltoides, and the materials in Fahrenkrog's study were mainly from the Mississippi River Basin [29,37]. Our research also showed that geographical isolation hindered gene exchange among individuals from different provenances and aggravated genetic differentiation.…”
Section: Genetic Diversity and Variationmentioning
confidence: 60%
See 2 more Smart Citations
“…Fahrenkrog et al [29] reported the first population genomics study for P. deltoides distributed in the Mississippi River Basin to determine its genetic diversity and adaptation potential. In the present study, we analyzed 384 P. deltoides individuals preserved in the germplasm bank, which were originally distributed in 27 collection sites for 6 provenances.…”
Section: Many Methods and Techniques Have Been Developed To Advance Pmentioning
confidence: 99%